The Role of School Administration Staff in Supporting the Implementation of The Kurikulum Merdeka - Aprilina, Magda; Triwiyanto, Teguh; Sultoni, Sultoni; Srikandi, Margaretha Dewi (Universitas Negeri Malang, 2024)
Indonesian education by implementing the Merdeka Curriculum is an important step in education reform. The Merdeka Curriculum aims to provide freedom in the learning and teaching process and prioritize the development of students' individual characters, skills and interests. School administrators are not only in charge of administrative aspects but also play a role as the main driver in fostering a conducive learning atmosphere. They play an important role in bridging curriculum policies and practices in the field, assisting teachers, students and parents in implementing Merdeka Curriculum principles. In implementing Merdeka Curriculum, school administrators function as facilitators who create a positive learning environment and support student development. Therefore, it is important to raise awareness about their roles and responsibilities in supporting the implementation of the Merdeka Curriculum. Another challenge faced by administrative personnel is the lack of training and resources to carry out their duties effectively.